Factors Related To The Incidence Of Diarrhea In Children Aged 0-60 Months In The Children's Inpatient Room Of Budi Kemuliaan Hospital In July-August In 2023 - Nabilian, Adisty; Suri Nurharjanti; Erina Windiany; Fitria Endah Purwani (Universitas STRADA Indonesia, 2024)
In Indonesia, diarrhea is the second leading cause of death in children under 5 years old. The prevalence of diarrhea in 2018 was 37.88% or around 1.516.438 cases in toddlers. Then, it increased in 2019 to 40% or around 1.591.944 cases in toddlers. The purpose of the study was to determine the factors associated with the incidence of diarrhea in children aged 0-60 months at Budi Kemuliaan Hospital in July-August 2023. This research method used descriptive analytical approach with a case control design. Data analysis was performed with Chi-Square and Fisher's Exact tests. The results o showed that there were seven variables that were related to the incidence of diarrhea (p<0,05) namely nutritional status, duration of exclusive breastfeeding, mother’s knowledge , measles vaccination status, ownership of latrines, mother’s education, and mother’s occupation.